Molecular Detection of Microsporum Canis Infection in Cats in Baghdad Governorate - Bidewy, Marwah Abdul Hassan; Hasso, Saleem Amin (South Eastern European Journal of Public Health, 2024)
Microsporum canis is a keratinized skin fungus that causes diseases in all animals, especially in cats. It is able to infected human causes Tinea corporis and Tinea capitis. In this study,the aim was toward detection and confirmation of Microsporum canis infection in cats in Baghdad governorate using polymerase chain reaction (PCR).The diagnosis depend on sequencing of the PCR products obtained by using a universal primer to amplification of the primer DppV which was 895 bp.A total of two hundred and eighty three hair and skin scraping samples were collected from infected cats with and without skin lesions. Preliminarily examined of samples with 10% KOH preparation, and cultured for fungal identification . For the culture; Saboruad dextrose agar was used . Culture results showed that four isolates were positive for M. canis , the best growth of these isolates was confirmed by PCR and DPPV gene then sequencing of this gene. PCR technique showed that one isolate from the total of 283 isolates were assured for the DPPV gene and yielded a band at 895 bp, this finding is regarded as distinctive for the genus Microsporum canis ,which was dumped in the GenBank nucleotide sequence database under accession number OR126262. Results sequencing of this gene in Iraq revealed compatibility with global results in USA and Belgium.